The United Nations Reform: an Analytical Look at its Problems and the Ways to Overcome them - Al-Wahshat, Ziad Muhammad (Journal of Legal Studies and Researches, 2021)
This research deals with the reform process of the United Nations, which has become one of the important topics as a result of the changes imposed by international relations on the international community, so it was necessary to reform the United Nations organs represented by the Security Council as responsible for maintaining global peace and security, and to reform the General Assembly due to the non-mandatory nature of its decisions, based on the principles of rule of law and respect for common interests.